Temporary recovery after resuscitation: delayed postanoxic encephalopathy. (15th April 2013) - Goedee, Stephan; van der Nat, Gerarda A M; Roks, Gerwin
Abstract : Delayed postanoxic encephalopathy is reported infrequently and is characterised by a lucid interval of seemingly good recovery from an anoxic insult. Days or even weeks may pass before changes in behaviour, motor responses or consciousness occur. Neurological deterioration may progress to coma, death or severe disability, whereas some patients have a second recovery period. Pathogenesis is yet to be discovered. Prognosis is reportedly poor, treatment is symptomatic and at best anecdotal. We present a case report and available literature.